Effect of Soaking Duration of Thermoplastic Nylon Denture Base in Arabica Coffee Solution (Coffea Arabica) on Color Changes - Sofya, Pocut Aya; Andriany, Poppy; Rahmayani, Liana; Ifwandi, Ifwandi; Namira, Adinda Sitti (Dentistry Faculty, 2024)
Background: Thermoplastic nylon is the denture base that dentists choose today. Thermoplastic nylon has a more aesthetic appearance in terms of color and does not use wire as a support. This thermoplastic nylon belongs to the polyimide class. This research aims to determine the effect of Arabica coffee drinks on changes in the base color of thermoplastic nylon dentures. Method: This type of research is laboratory experimental. The number of samples consisted of 24 samples divided into four treatment groups, two control groups in distilled water, and two immersion groups in Arabica coffee. The samples were immersed in the solution for 7 days and 14 days. The research data did not show changes in hue values, but there were changes in value and chroma values. The results: measuring value and chroma using the Kruskal-Wallis analysis test showed a significant color change of P = 0.00 (P 0.05). The results of the data analysis show that immersing thermoplastic nylon in an arabica coffee (Coffea arabica) environment on the value and chroma affects the color change of thermoplastic nylon denture elements. The conclusion: this study shows that there is an effect of changing the base color of thermoplastic nylon dentures when soaked in arabica coffee (Coffea arabica) solution.